Conceptualising the episodic nature of disability among adults living with Long COVID: a qualitative study. Issue 3 (2nd March 2023) - O'Brien, Kelly K; Brown, Darren A; McDuff, Kiera; St. Clair-Sullivan, Natalie; Solomon, Patricia; Chan Carusone, Soo; McCorkell, Lisa; Wei, Hannah; Goulding, Susie; O'Hara, Margaret; Thomson, Catherine; Roche, Niamh; et al.
Abstract : Introduction: Our aim was to describe episodic nature of disability among adults living with Long COVID. Methods: We conducted a community-engaged qualitative descriptive study involving online semistructured interviews and participant visual illustrations. We recruited participants via collaborator community organisations in Canada, Ireland, UK and USA. We recruited adults who self-identified as living with Long COVID with diversity in age, gender, race/ethnicity, sexual orientation and duration since initial COVID infection between December 2021 and May 2022. We used a semistructured interview guide to explore experiences of disability living with Long COVID, specifically health-related challenges and how they were experienced over time. We asked participants to draw their health trajectory and conducted a group-based content analysis. Results: Among the 40 participants, the median age was 39 years (IQR: 32–49); majority were women (63%), white (73%), heterosexual (75%) and living with Long COVID for ≥1 year (83%). Participants described their disability experiences as episodic in nature, characterised by fluctuations in presence and severity of health-related challenges (disability) that may occur both within a day and over the long-term living with Long COVID. They described living with 'ups and downs', 'flare-ups' and 'peaks' followed by 'crashes', 'troughs' and 'valleys', likened to a 'yo-yo', 'rolling hills' and 'rollercoaster ride' with 'relapsing/remitting', 'waxing/waning', 'fluctuations' in health. Drawn illustrations demonstrated variety of trajectories across health dimensions, some more episodic than others. Uncertainty intersected with the episodic nature of disability, characterised as unpredictability of episodes, their length, severity and triggers, and process of long-term trajectory, which had implications on broader health. Conclusion: Among this sample of adults living with Long COVID, experiences of disability were described as episodic, characterised by fluctuating health challenges, which may be unpredictable in nature. Results can help to better understand experiences of disability among adults living with Long COVID to inform healthcare and rehabilitation.